Penerapan Augmented Reality pada Sistem Operasi Android untuk Pengenalan Profesi terhadap Anak Usia Dini - Rabbani, Irsyad; Oktaviani, Maria Rosaria; Shobirin, Muhammad Ilham; Sakti, Dolly Virgian Shaka Yudha (Jurusan Informatika Universitas Tanjungpura, 2020)
Children are interested in new things, interactive, motivate, and fun things that can be used for the learning system. Nowadays, the system of traditional learning such as books and toys are not effective to make children interest to use. Technology must be included in the learning system which is can be able to introduce the function and usefulness of the technology for children. Children's knowledge about the future of professions that can be used as their goal life is still limited. Meanwhile, there are kinds of professions that children must know with the result that they have more insight into the world and know what talent they have which is can become a profession in the future. Augmented Reality is a technology that makes virtual objects possible to be seen in 3 dimensions and as in reality. By determine marker or image that will be the target of a smartphone camera, that marker will result in a 3-dimensional shape on the smartphone screen if the camera was pointed at the marker. This research was conducted with interviews and application trials. We conducted intense interviews with several children under 5 years as a reference for understanding about profession.